KONTRIBUSI RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP PENINGKATAN PRICE TO BOOK VALUE (Penelitian di Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2014-2023) - Nurul Izzah Ravelina; Zia Sidqurrahman; Budi Budiman (Lobi, 2025)
Price to Book Value (PBV) is a ratio used to compare a company's market value with its book value. The high or low PBV is influenced by various factors, such as profitability, capital structure, revenue growth, and investor confidence, where a high PBV indicates better business prospects. This study aims to determine the effect of Return on Asset (ROA) and Debt to Equity Ratio (DER) on Price to Book Value (PBV). The research method uses a descriptive verification method with a quantitative approach. Data used in this study Based on panel data regression analysis, simultaneous test (f test) and partial test (t test), the test results show that ROA has a significant effect on PBV, and DER has a significant effect on PBV.